Begum Akhtar Riaz Ud Din:A Feminist Travelogue Writer - Dr. Sabina Awais; Dr. Muhammad Afzal But; Dr. Saira Batool (Zaban-o-Adab, 2021)
“Safar Nama” is a literary term which is basically a complete description of various events in writings, take place during any traveling. It is such type of “Nasr” in which a writer or artist tells his observations and experiences in a detailed way. Safar Nama is not an old genre in Urdu literature. It started with the writings of Yusuf Khan Kambal Posh known as “AJAIBAAT FARANG”. In nineteenth century, it remained a low rated and least considered genre of Urdu literature. In twentieth century, it found momentum and caught contribution not from males but also from females. Begum Akhtar Riaz udin is also one of such blue stockings who richly contributed in this genre. Two Safar Nama like “Samadar Paar” and “Dhanak Per Qadam” were also written by Begum Akhtar. Her writings are complete in agreement with latest developments in “Safar Namas”. These pieces of writings reflect deep observations, humor, decent approach and feministic way of expressions. She traveled across to Tokyo, Masco, Cairo, London, New York, Jazair, Hawai, Mexico and Hong Kong and put a mature eye on these places. She described different cultural and social aspects of these places and brought them to light. Feminism can easily be traced down in her writings. She observed women of every country with a close eye and produced her opinion about their life style in a very keen way. This article will encompass her writings and observations of her world tours.